The Effect of Chronic Illness on Participation in the Supplemental Nutrition Assistance and Medicaid Programs. (1st October 2014) - Meyerhoefer, Chad D.; Pylypchuk, Yuriy
Abstract : We examine enrollment in the U.S. Medicaid and Supplemental Nutrition Assistance Programs (SNAP) and find that while SNAP‐eligible adults in poor physical health and with multiple chronic conditions are more likely to jointly enroll in SNAP and Medicaid, they are less likely to enroll in SNAP alone. We also find that the conditional probability of SNAP enrollment given Medicaid participation is higher for individuals with multiple chronic conditions. As a result, the expansion of Medicaid and state policies that promote enrollment coordination between SNAP and Medicaid are expected to increase the number of individuals in SNAP with chronic medical conditions.